Permafrost studies in northern Québec - Taylor, Alan; Judge, Alan (Géographie physique et Quaternaire, 1979)
In cooperation with mining companies, temperature data are being acquired at several sites in the Cape Smith — Wakeham Bay Belt of Northern Québec. Cables, containing up to twenty thermistors, are lowered into exploratory diamond-drill holes upon completion, and allowed to freeze in place. Three temperature profiles at Asbestos Hill yield low geothermal gradients; thermal conductivities of core are moderate to low and hence low values of the terrestrial heat flow are observed. Extrapolating temperature profiles to greater depths gives a permafrost thickness of at least 540 m. The uncorrected terrestrial heat fluxes calculated for the shallow holes are about 2/3 that of the lower section of the deeper hole. Such contrast in heat flow is used to develop a simple model of surface temperature history for the area for the past 85 000 years. Using this geothermal data, engineering estimates may be made of such parameters as maximum active layer thickness and thaw penetration of both open pit walls and underground drifts.